Determining the effects of thermal conductivity on epoxy molds using profiled cooling channels with metal inserts - Altaf, K. (Korean Society of Mechanical Engineers, 2016)
Polymer injection molds are generally manufactured with metallic materials, such as tool steel, which provide reliable working of molds and extended service life. The manufacture of injection molds with steel is a prolonged process because of the strength of steel. For a short prototype production run, one of the suitable choices could be the use of aluminum-filled epoxy material, which can produce a functional mold in a short time as compared with a conventionally machined tool. Aluminum-filled epoxy tooling is a good choice for short production runs for engineering applications, yet works best for relatively simple shapes. The advantages in relation to the fabrication of injection molds with epoxy-based materials include time saving in producing the mold, epoxy curing at ambient temperature, and ease of machining and post processing. Nevertheless, one major drawback of epoxy material is its poor thermal conductivity, which results in a relatively longer cooling time for epoxy injection molds. This study investigates some of the innovative ideas for enhancing the thermal conductivity for epoxy molds. The basic concept behind these ideas was to embed a highly thermally conductive metal insert within the mold between cavities with an innovative design of cooling channels called profiled cooling channels. This technique will increase the effective thermal conductivity of the epoxy mold, leading to the reduction in cooling time for the injection molded polymer part. Experimental analysis conducted in the current study also verified that the mold with profiled cooling channels and embedded metal insert has significantly reduced the cooling time. Â© 2016, The Korean Society of Mechanical Engineers and Springer-Verlag Berlin Heidelberg.